Country compliance with WHO-recommended antenatal care guidelines: equity analysis of the 2015–2016 Demography and Health Survey in Myanmar - Camille Raynes-Greenow; Ngatho Samuel Mugo; Kyaw Swa Mya (BMJ Global Health)
Introduction Early access to adequate antenatal care (ANC) from skilled providers is crucial for detecting and preventing obstetric complications of pregnancy. We aimed to assess factors associated with the utilisation of the new WHO ANC guidelines including the recommended number, on time initiation and adequate components of ANC contacts in Myanmar.Methods We examined data from 2943 mothers aged 15–49 years whose most recent birth occurred in the last 5 years prior to the 2015–2016 Myanmar Demographic and Health Survey. Factors associated with utilisation of the new WHO recommended ANC were explored using multinomial logistic regression and multivariate models. We used marginal standardisation methods to estimate the predicted probabilities of the factors significantly associated with the three measures of ANC.Results Approximately 18% of mothers met the new WHO recommended number of eight ANC contacts. About 58% of the mothers received adequate ANC components, and 47% initiated ANC within the first trimester of pregnancy. The predicted model shows that Myanmar could achieve 70% coverage of adequate components of ANC if all women were living in urban areas. Similarly, if ANC was through private health facilities, 63% would achieve adequate components of ANC. Pregnant women from urban areas (adjusted risk ratio (aRR): 4.86, 95% CI 2.44 to 9.68) were more than four times more likely to have adequate ANC components compared with women from rural areas. Pregnant women in the highest wealth quintile were three times more likely to receive eight or more ANC contacts (aRR: 3.20, 95% CI 1.61 to 6.36) relative to mothers from the lowest wealth quintile. On time initiation of the first ANC contact was fourfold for mothers aged 30–39 years relative to adolescent mothers (aRR: 4.07, 95% CI 1.53 to 10.84).Conclusion The 2016 WHO ANC target is not yet being met by the majority of women in Myanmar. Our results highlight the need to address health access inequity for women who are from lower socioeconomic groups, or are younger, and those living in rural areas.